Next-Generation Solid-State Quantum Emitters - Sherlekar, Nachiket Sunil (University of Waterloo, 2019)
This thesis details two types of deterministic solid-state quantum emitters, an optically-driven quantum dot source in a tapered nanowire waveguide, and an electrically-driven source implemented by integrating a single-electron pump into a two-dimensional p-n junction. A finite-difference time-domain model of the optically-driven nanowire quantum dot source yielded optimized architectural parameters required to obtain a high transmission efficiency and a Gaussian far-field emission profile. An additional model of an electrically-gated nanowire source examined the effect of the surrounding structures on the emission properties of the source. A successfully working prototype p-n junction device as a precursor to the electrically-driven quantum emitter was implemented by simultaneously inducing positive and negative two-dimensional carrier gases in an undoped semiconductor heterostructure. This device, fabricated in-house, offers a path forward in the development of a new class of bright, deterministic sources of single- and entangled-photons.
Keywords: single photon source; nanophotonics; entanglement; quantum dot; nanowire; p-n junction; simulation; fabrication; Nanophotonics; Quantum entanglement; Quantum dots; Nanowires; Quantum optics